Early Right Heart Chambers Reverse Remodeling in Patients Operated in Adulthood for Congenital Lesions Associated with Right Heart Chambers Enlargement. Issue 6 (November 2021) - Panaioli, Elena; Graziani, Francesca; Lillo, Rosa; Delogu, Angelica Bibiana; Grandinetti, Maria; Di Molfetta, Arianna; Perri, Gianluigi; Pasquini, Annalisa; Colizzi, Christian; Lombardo, Antonella; Locorotondo, Gabriella; Amodeo, Antonio; et al.
Background: Progressive right heart chambers dilatation is frequent in the adult congenital heart disease (ACHD) population. We evaluated the immediate and mid-term response of right heart chambers to surgery performed in adulthood for lesions associated with right heart chambers enlargement. Methods: Thirty-six adult patients with lesions associated with right heart chambers enlargement submitted to surgery were studied . We collected echocardiographic data of right ventricle (RV) mid-diameter, right atrial volume indexed, RV systolic pressure, and tricuspid annular plane systolic excursion (TAPSE) prior to surgery (T0), at 2 to 5 days (T1), and 3 to 6 months (T2) after surgery. Results: At T1, we observed a significant decrease of RV mid-diameter (47.2 ± 8.4 vs. 39.6 ± 7.4 mm, P < .001), right atrial volume indexed (45.6 ± 26.6 vs. 27.2 ± 11 ml/m2, P < .001), and RV systolic pressure (39 ± 14.8 vs. 32.8 ± 11.3 mm Hg, P = .03). At T2, a further significant deviation in the rate of RV diameter (39.6 ± 7.4 vs. 34.5 ± 5.1 mm, P < .001), in RV systolic pressure (32.8 ± 11.3 vs. 25.3 ± 5 mm Hg, P = .03) and TAPSE (13.9 ± 3.2 vs. 15.8 ± 2.6 mm, P < .001) was observed. Conclusions: Positive right heart chambers remodeling occurs as early as in the immediate post-operative period in most ACHD patients operated for lesions associated with right heart chambers enlargement.